The Effectiveness of Supervision Programs on Improving Teaching Skills and Teacher Performance - Agustina Said (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to evaluate the effectiveness of the academic supervision program in improving teaching skills and teacher performance at SMK Muhammadiyah 1 Sangatta Utara. Using a quantitative approach and experimental design, the study involved 30 teachers as respondents, where 60% had less than 5 years of teaching experience, and 40% had more than 5 years of experience. Data were collected through standardized observation instruments and analyzed using t-test and regression analysis. The results showed a significant increase in teachers' teaching skills by 23.08% (from a score of 65 to 80) and teacher performance by 21.43% (from a score of 70 to 85) after the implementation of the supervision program. The statistical analysis produced a t-value of 5.67 with a p-value <0.05 and a coefficient of determination (R²) of 0.62, indicating that 62% of the variation in teacher performance can be explained by the supervision program. The majority of teachers expressed high satisfaction with the supervision program in providing an understanding of learning objectives (85%), improving teaching skills (90%), providing constructive feedback (88%), encouraging creativity (87%), and increasing collaboration between teachers (80%). Factors supporting the effectiveness of supervision include the frequency of periodic supervision, collaborative supervision methods, school management support, and teacher self-reflection. This study has important implications for the development of an adaptive supervision model for vocational education and can be an empirical reference for similar educational institutions in designing effective and sustainable teacher professionalism improvement programs